MANAJEMEN PENDIDIKAN ISLAM DI PESANTREN: PERSPEKTIF EPISTEMOLOGI - Rahmatun Lukluk Isnaini (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
Management of Islamic education in pesantren needs to return to its historical roots in order to confirm the identity, character, distinctiveness and uniqueness. There is a spirit that is timeless, even the underlying model of ideal education in the contemporary era. Development of Islamic epistemology for education should be able to give birth to a generation of Muslims who worships in the field of religion and experts in the field of science and technology. pesantren as an educational institution of Islam with a good management should be able to play its role to achieve this goal. Whereas in fact there who think that pesantren have not been able to put its strategic position in the development of science in accordance with the times. Nevertheless, the existence of Islamic educational institutions such as pesantren is evidence that pesantren have been organized in a good management so that it can survive in changing times from time to time. More precisely knowing Islamic education management in pesantren from the perspective of epistemology may illustrate that pesantren will continue to be needed to confront the changing times.